Decisions at Stones River : The Sixteen Critial Decisions that Defined the Battle - Spruill, Matt; Spruill, Lee (Book collections on Project MUSE., 2018)
From December 31, 1862, to January 2, 1863, the Army of the Cumberland and Army of Tennessee fought a bloody battle along Stones River. Led by Major General William S. Rosecrans, Union forces would eventually emerge victorious. Coming at the end of a series of Union defeats, this victory would give Lincoln and the Northern population a ray of hope during a fall and winter of reversals. Decisions at Stones River introduces readers to critical decisions made by Confederate and Union commanders. This account is designed to present the reader with a coherent and manageable blueprint of the battle's development. Rather than offering a history of the Battle of Stones River, Matt Spruill and Lee Spruill examine the decisions that shaped the way the battle unfolded. Exploring and studying the critical decisions allows the reader to progress from an understanding of "what happened" to "why events happened" as they did. Complete with maps and a guided tour, Decisions at Stones River is an indispensable primer, and readers looking for a digestible introduction to the Battle of Stones River can tour this sacred ground--or read about it at their leisure--with key insights into the battle and a deeper understanding of the Civil War itself. -- Back cover.